"Little Fresh Meat": The Politics of Sissiness and Sissyphobia in Contemporary China. (April 2022) - Song, Geng
The proliferation of effeminate male images known as "little fresh meat" ( xiao xian rou ), or, more insultingly, "sissy pants" ( niangpao ) in film, TV, and advertisement has come in for heavy criticism in China. A number of "sissy" actors have even been blacklisted by the state media. Yet, despite this masculinist backlash, effeminate-looking stars and the aesthetic they embody are enjoying increasing popularity among high school students and other young people in urban China. The article situates the prevalence of male effeminacy and "sissyphobia"—the fear or hatred of effeminate men—in a wider social, cultural, and political background and adopts a culturally saturated and historically specific approach to queer masculinities in the Chinese context. By critical readings of recent TV/Web dramas featuring this type of male images, the article explores the disjuncture between urban youth culture and official attitudes and what the tension between them tells us about gender roles and subjectivity in contemporary China. And by discourse analysis of the debates in the media triggered by the images, the study examines how the effeminate male body is given affective interpretations and significances that are different from those in a Western context, and how the nation is imagined and articulated through embodied masculinity. Through an interdisciplinary approach, the article argues that the "little fresh meat" is part of a larger story of increasing diversity of gender presentations in postsocialist China and embodies shifting masculinity in a consumer society. The rise and popularity of such "sissy" actors need to be understood in the mechanisms of star making and the entertainment industry. At the same time, the debates on the standard of masculinities sparked by these images demonstrate distinctive interplay between manhood and nationhood and deep-seated anxiety over what an effeminate younger generation will mean for China.